A first course in fuzzy logic - Nguyen, Hung T. (Chapman & Hall, 2006)
A First Course in Fuzzy Logic, Third Edition continues to provide the ideal introduction to the theory and applications of fuzzy logic. This best-selling text provides a firm mathematical basis for the calculus of fuzzy concepts necessary for designing intelligent systems and a solid background for readers to pursue further studies and real-world applications. New in the Third Edition: · A section on type-2 fuzzy sets - a topic that has received much attention in the past few years · Additional material on copulas and t-norms · More discussions on generalized modus ponens and the compositional rule of inference · Complete revision to the chapter on possibility theory · Significant expansion of the chapter on fuzzy integrals · Many new exercises With its comprehensive updates, this new edition presents all the background necessary for students and professionals to begin using fuzzy logic in its many-and rapidly growing- applications in computer science, mathematics, statistics, and engineering.